Forward and back: kinematics of the Palomar 5 tidal tails. Issue 1 (14th February 2022) - Kuzma, P B; Ferguson, A M N; Varri, A L; Irwin, M J; Bernard, E J; Tolstoy, E; Peñarrubia, J; Zucker, D B
ABSTRACT: The tidal tails of Palomar 5 (Pal 5) have been the focus of many spectroscopic studies in an attempt to identify individual stars lying along the stream and characterize their kinematics. The well-studied trailing tail has been explored out to a distance of 15 ○ from the cluster centre, while less than 4° have been examined along the leading tail. In this paper, we present results of a spectroscopic study of two fields along the leading tail that we have observed with the AAOmega spectrograph on the Anglo-Australian telescope. One of these fields lies roughly 7 ○ along the leading tail, beyond what has been previously been explored spectroscopically. Combining our measurements of kinematics and line strengths with Pan-STARRS1 photometric data and Gaia EDR3 astrometry, we adopt a probabilistic approach to identify 16 stars with a high probability of belonging to the Pal 5 stream. Eight of these stars lie in the outermost field and their sky positions confirm the presence of 'fanning' in the leading arm. We also revisit previously published radial velocity studies and incorporate Gaia EDR3 astrometry to remove interloping field stars. With a final sample of 109 bona fide Pal 5 cluster and tidal stream stars, we characterize the 3D kinematics along the the full extent of the system. We provide this catalogue for future modeling work.